(untitled) (AYUSHDHARA, 2016)
Prakriti is the health profile or unique psychosomatic temperament of an individual encompassing his or her physical, functional and behavioural characteristics. Prakriti is not only an instrument to examine the patient but also influences the onset, occurrence, pathogenesis, diagnosis, prognosis and management of a patient. Among the various specific characteristics of Ayurveda, the knowledge of ‘Prakriti’ is at the top. Charaka, while directing tenfold examination of a patient (Dasvidh Pariksha), has counted ‘Prakriti’ on the top. Prakriti is most important in achieving the goal of Ayurveda, i.e. the maintenance of health of a healthy individual and cure of a diseased person. Keeping the knowledge of Prakriti in mind, a physician can suggest the person to follow up the day, night and seasonal regimens for the maintenance of health. Not only this, a diseased person can be easily managed by the knowledge of the Prakriti in the diagnosis as well as treatment. The knowledge of Prakriti eases the process of management of a disease because according to Ayurvedic concept, no disease in the body is possible without involvement of Dosha and the management is the reestablishment of Doshas in their normal state. For the purpose of present study, 30 patients of Sandhivata were selected from OPD and IPD of Ayurvedic and Unani Tibbia College Hospital and from Multi-Speciality Hindustani Dawakhana, Delhi having complaints related to ‘Sandhivata as per the “criteria for the selection of the patients” given below. On the basis of clinical examination (signs & symptoms) and necessary investigation (X-ray of the involved joints), the diagnosis of Sandhivata was established, then the patients were included in the study. The Prakriti of each patient was identified with the help of standard proforma, based on various signs & symptoms presented by various Ayurvedic authors for this purpose. The study revealed that Sandhivata has predominance in Vata pradhan prakriti due to Samanaya siddhanta.